Profile of Thin-Layer Chromatography and UV-Vis Spectrophotometry of Akar Kuning Stem Extract (Arcangelisia flava) - Mohammad Rizki Fadhil Pratama; Suratno Suratno; Evi Mulyani (Borneo Journal of Pharmacy, 2018)
This study aims to obtain the profile of Thin-Layer Chromatography (TLC) and Ultraviolet-Visible (UV-Vis) spectrophotometry from the ethanol extract of akar kuning stems (Arcangelisia flava) from Central Kalimantan. The TLC method is used with the orientation phase of the combination of polar-non-polar solvents resulting from orientation, while ethanol is used as the solvent for UV-Vis spectrophotometers. TLC results showed the formation of three stains on a mixture of polar solvents chloroform : methanol : water while in a non-polar solvent combination n-hexane : ethyl acetate did not show any stains. Comparison of retention factor (Rf) values shows the best combination of polar solvents to separate stains at a ratio of 5 : 2 : 1, respectively. Separation in 2-dimensional TLC with polar solvents showed a similar pattern with 1-dimensional separation in the form of three stains. UV-Vis spectrophotometer results showed four main peaks with wavelength 227.2; 267.4; 345.2; and 425.3 nm, respectively. The profile of the peak formed is very similar to that shown by berberine, one of the primary metabolites of akar kuning. TLC and UV-Vis spectrophotometers profiles obtained are expected to support further research using akar kuning stems, especially those from Central Kalimantan.